A highly selective fluorescent sensor for the detection of Al3+ and CN− in aqueous solution: biological applications and DFT calculations. (21st September 2016) - Jo, Tae Geun; Lee, Jae Jun; Nam, Eunju; Bok, Kwon Hee; Lim, Mi Hee; Kim, Cheal
Abstract : A new turn-on fluorescent chemosensor1 was developed to detect both Al 3+ and CN − and used for practical and biological applications. Abstract : A new "turn-on fluorescence type" chemosensor1 ( N ′1, N ′2-bis(( E )-2-hydroxybenzylidene)oxalohydrazide) with a simple structure was devised and synthesized. In aqueous solution, receptor1 could efficiently detect both Al 3+ and CN − at two different wavelengths. The limit of detection for Al 3+ (2.0 μM) is below the World Health Organization (WHO) guideline for drinking water (7.41 μM). To utilize for practical and biological applications, the ability of1 for monitoring Al 3+ was tested in real water samples and living cells. In addition, 1 showed a highly selective fluorescence enhancement for CN − in the presence of other anions without any interference. The sensing mechanisms of1 for Al 3+ and CN − were supported by theoretical calculations.